2006
DOI: 10.1186/1897-4287-4-1-15
|View full text |Cite
|
Sign up to set email alerts
|

The NOD2 3020insC Mutation in Women with Breast Cancer from the Bydgoszcz Region in Poland. First Results

Abstract: The frameshift NOD2 gene mutation 3020insC is predominantly associated with Crohn's disease, but predisposes to many types of common cancers as well. We studied the frequency of this mutant NOD2 allele in 148 breast cancer women from the Bydgoszcz region in Poland. The NOD2 mutation was present in 8.8% of the patients. The mean age at breast cancer diagnosis of the mutation carriers was 43 years. We did not find any mutation in patients diagnosed with breast cancer after the age of 50 years. There was no assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…Others calculated that the mutation's frequency (11.4%) was two times higher in women of families with a single case of BC. 29 A c.5972C>T polymorphic variant in the BRCA2 is present in 8.3% of unselected BC patients diagnosed at 40 or less, and especially in those with DCIS with microinvasion, as was the case of our patient. Heterozygotes (C/T) for c.5972C>T in BRCA2 are at a 3-fold risk for DCIS BC before 50 compared with a 5-fold risk for homozygous (T/T) carriers.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Others calculated that the mutation's frequency (11.4%) was two times higher in women of families with a single case of BC. 29 A c.5972C>T polymorphic variant in the BRCA2 is present in 8.3% of unselected BC patients diagnosed at 40 or less, and especially in those with DCIS with microinvasion, as was the case of our patient. Heterozygotes (C/T) for c.5972C>T in BRCA2 are at a 3-fold risk for DCIS BC before 50 compared with a 5-fold risk for homozygous (T/T) carriers.…”
Section: Discussionsupporting
confidence: 71%
“…Huzarski et al established that this NOD2 founder mutation is relatively common in Poland, present in 7.3% of the general population and may be responsible for a significant proportion of breast, colon, lung, larynx, and ovarian cancers. 27 The NOD2 c.3020insC allele was found in approximately 8% of all BCs 29,30 and in 13.2% of cases diagnosed before the age of 50. 27,28 A c.3020insC in NOD2 increases the risk of DCIS-bearing BC below age 50 about 5-fold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2005, two studies conducted in the Polish population [65,106] showed the correlation between the insertion allele of rs2066847 polymorphism and higher risk of ductal breast cancer in situ, and in one of them [106] the additional connection with early-onset breast cancer was noted. The similar association with breast cancer arising before 50 years of life was also observed by Irmejs et al [67] in Latvian population and by Janiszewska et al [107] in another Polish population. For ovarian cancer, results are conflicting: Whereas Lubinski et al [65] found an association of the insertion allele of the rs2066847 polymorphism with increased ovarian cancer, Magnowski et al [108] observed no correlation.…”
Section: Nod2/card15 Gene Polymorphisms and Risk Of Gynecologic Cancesupporting
confidence: 68%
“…Other clinicopathological factors were also analyzed. Janiszewska et al (31) did not report any NOD2 mutations in patients diagnosed with breast cancer after the age of 50 years. There was no reported association between NOD2 mutations and a strong family history of breast cancer.…”
Section: Discussionmentioning
confidence: 98%